”Pinch and Stretch” technique to overcome ocular hypotony during scleral suturing of recti muscles - Amar Pujari; Bhupender Yadav; Sujeeth Modaboyina (Indian Journal of Ophthalmology, 2023)
During extraocular muscle surgery, an uneventful scleral suture pass is very essential. In presence of normal intraocular tension, the surgery is quite predictable and safe. However, in the presence of significant hypotony, it becomes challenging. Therefore, to mitigate complication rate in these cases, we have adopted a simple technique, that is, the “pinch and stretch” technique. The surgical steps of this technique are as follows: In eyes with significant ocular hypotony, the surgery is initiated with a routine forniceal/limbal peritomy, following which the muscle is sutured and dis-inserted. Using three tissue fixation forceps, the scleral surface is stabilized. Using first forceps, the surgeon rotates the globe toward themself from the muscle stump, and with the remaining two forceps, the assistant pinches and stretches the episcleral tissue in an outward and upward direction just beneath the intended marks. This creates a flat scleral surface with significant firmness. Sutures are passed over this rigid sclera and the surgery is completed without any complications.